Speaking about torture - Carlson, Julie Ann, 1955-; Weber, Elisabeth, 1959- (Fordham University Press, 2012)
This collection of essays take up the urgent issue of torture from the array of approaches offered by the arts and humanities. The book speaks about the practice in an effort to challenge the surprisingly widespread acceptance of state-sanctioned torture among Americans.